A1.25 B-Cell profile in RA patients treated with two different biological therapeutic targets: anti-TNF and anti-IL6R. a cross-sectional study. (31st January 2014) - Hernández, Diana; Valor, Lara; de la Torre, Inmaculada; del Río, Tamara; Martinez, Lina; Naredo, Esperanza; González, Carlos; Lopez-Longo, Javier; Monteagudo, Indalecio; Montoro, María; Carreño, Luis
Abstract : Background: B-cells play a cardinal role in the pathogenesis of rheumatoid arthritis (RA) as demonstrated by the effectiveness of B-cell depletion with rituximab (RTX). In the current cross-sectional study, we assessed the phenotypical changes of B-cell subsets in RA patients treated with different anti-cytokine therapeutic targets, anti-TNF: infliximab (IFX), adalimumab (ADA), etanercept (ETA) and the anti-IL6R: tocilizumab (TCZ), compared to healthy controls (HC). Patients and Methods: We assessed B cells expressing BBR: BAFF-R, TACI, BCMA and the activation marker CD86 in peripheral blood in a total of 108 patients with RA treated with IFX (n = 37), ADA(n = 28), ETA(n = 28), and TCZ (n = 14) as well as on HC (n = 19). Clinical status of patients was determined using the 28 joints disease activity score (DAS28), defining non-remission as DAS28>3.2, and remission as DAS28<2.6. Multiparametric flow cytometry was performed using monoclonal antibodies to CD19, CD27, CD38, IgD, BAFF-R, TACI, BCMA and CD86. Results: We found that the frequency of both naïve (CD19 + /CD27-) and memory B-cells (CD19 + /CD27 + ) in all RA treatment groups was similar to HC independently of RA disease activity and treatmet. Regarding B cell subsets, percentages of transitional B cells were higher in TCZ than ADA (p = 0.002) and HC (p = 0.03 and p = 0.001) groups while memory resting B cell were higher in ADA group compared to HC (p = 0.007, and p = 0.01) in active and inactive patients. Percentages of naïve B-cells expressing BAFF-R and TACI were similar in all groups, while memory B-cells expressing TACI were similar to HC in inactive patients on TCZ. About BCMA expression on memory B cells, TCZ was similar to HC in active patients. CD86 expression was higher in active patients on TCZ compared to HC (p<0.0001) and ADA (p = 0.02) groups. Conclusions: Our findings show that the reduced frequency of memory B-cells expressing TACI and BCMA present in those patients treated with TCZ might indicate a possible extra effect on B-cell phenotype and receptors and therefore on their survival and maturation process, not yet demostrated using anti-TNF-a therapies, which could be a further indicator to define therapy success and/or failure in RA patients.